Effects of meteoric smoke particles on the D region ion chemistry. Issue 12 (15th December 2015) - Baumann, Carsten; Rapp, Markus; Anttila, Milla; Kero, Antti; Verronen, Pekka T.
Abstract: This study focuses on meteor smoke particle (MSP) induced effects on the D region ion chemistry. Hereby, MSPs, represented with an 11 bin size distribution, have been included as an active component into the Sodankyä Ion and Neutral Chemistry model. By doing that, we model the diurnal variation of the negatively and positively charged MSPs as well as ions and the electron density under quiet ionospheric conditions. Two distinct points in time are studied in more detail, i.e., one for sunlit conditions (Solar zenith angle is 72°) and one for dark conditions (Solar zenith angle is 103°). We find nightly decrease of free electrons and negative ions, the positive ion density is enhanced at altitudes above 80 km and reduced below. During sunlit conditions the electron density is enhanced between 60 and 70 km altitude, while there is a reduction in negative and positive ions densities. In general, the MSP influence on the ion chemistry is caused by changes in the electron density. On the one hand, these changes occur due to nightly electron scavenging by MSPs resulting in a reduced electron‐ion recombination. As a consequence positive ion density increase, especially water cluster ions are highly affected. On the other hand, the electron density is slightly increased during daytime by a MSP‐related production due to solar radiation. Thus, more electrons attach to neutrals and short‐lived negative ions increase in number density. The direct attachment of ions to MSPs is a minor process, but important for long living ions. Key Points: Ionospheric modeling of the D region ion chemistry including meteor smoke particles Diurnal variations of charged MSP number density and plasma composition differences Case studies during sunlit and dark conditions for the analysis of individual ion behavior